In-situ transmission electron microscopy analysis of the degree of heterogeneities in a metallic glass. (March 2023) - Zhang, N.Z.; Sun, K.; Şopu, D.; Spieckermann, F.; Ma, X.D.; Geng, C.; Bian, X.L.; Jia, Y.D.; Wang, Q.; Wang, G.; Eckert, J.
Abstract: The most common strategy to enhance the plasticity of metallic glasses (MGs) is to synthesize MG composites with crystalline phases. Here, the evolution of crystallization and the correlation between void-like defects and crystallization for the as-spun and cryogenically-treated (CT) MGs are investigated under a rigorous annealing process conducted in-situ . The as-spun specimen maintains its amorphous structure with a relatively large size of nanoscale defects. However, crystallization is observed for the CT MG with a high concentration of nanoscale defects that decreases during the crystallization process. The crystallization develops readily in the CT MG due to the greater size of the ordered clusters, the higher concentration of seeding sites, and its greater nucleation rate. Our findings demonstrated cryogenic treatment could tune atomic rearrangements, which has guiding significance on designing MG composite with controlled length scales and distribution of crystalline inclusions. Graphical abstract: Image 1 Highlights: During in-situ annealing process, the as-spun MG maintains its amorphous structure, but crystallization is observed for the cryogenic-treated MG. The evolution of crystallization and the correlation between defects and crystallization at the nanoscale is accordingly investigated. Our work provides a new perspective for understanding the structural information featured in disordered materials, and contributes toward a more complete understanding of the primary crystallization mechanisms in MGs.